2018
DOI: 10.21003/ea.v170-03
|View full text |Cite
|
Sign up to set email alerts
|

Integral assessment of the sustainable development of agriculture in Ukraine

Abstract: Introduction. An integrated assessment of the accounting and analytical supplying indicators for the sustainable development of agricultural enterprises is the basis and starting point for the development of methodical and methodological background for the compilation of non-financial or expanded financial reports supplemented by social and environmental data of agricultural enterprises' external and internal activities. The purpose of the article is to develop a cross-functional procedure for the integrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
(10 reference statements)
0
13
0
1
Order By: Relevance
“…However, unlike the results published in paper [13], the obtained data on the assessment of the level of management of development of coke chemical enterprises enable asserting the following. The system of indicator estimates of the CP includes indicators for the development components (economic, social, environmental and energy) and spheres of activity.…”
Section: Discussion Of Results Of Development and Approbation Of The mentioning
confidence: 67%
See 1 more Smart Citation
“…However, unlike the results published in paper [13], the obtained data on the assessment of the level of management of development of coke chemical enterprises enable asserting the following. The system of indicator estimates of the CP includes indicators for the development components (economic, social, environmental and energy) and spheres of activity.…”
Section: Discussion Of Results Of Development and Approbation Of The mentioning
confidence: 67%
“…The most popular method for assessing the development of a country, regions, industries and enterprises is the integrated method. The authors of [13] determine that many indicators should be used to assess the enterprise development, so the method of standardization of the integrated indicator is proposed. However, two approaches are used in the formation of indicators -quantitative and intuitive, which is of subjective nature.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Numerous studies have shown that the network contributes significantly to SMEs' internationalization and the three types of networks-social networking, business networking, and institutional networking-play different roles in this phenomenon. In the initial stages of internationalization, social networks have a more considerable influence, while business networks become more relevant in subsequent stages, and then institutional networks have a positive impact on the internationalization of SMEs as well (Costa et al, 2017;Nyuur et al, 2018;Sokil et al, 2018;Hao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it can be underlined that the concept of the electronic agricultural purchasing marketplace may work anywhere that embodies a novel approach to today's agriculture based on modern technologies offering an opportunity to both agricultural producers and suppliers (Vasa, 2011;Erdeiné Késmárki-Gally, 2018;Sokil et al, 2018). However, in case of Vietnam, the situation is more complex as the market-oriented companies and improving market-friendly regulations are sometimes in contrast with the "old school" socialist political guidelines and leadership.…”
Section: Introductionmentioning
confidence: 99%